1984
DOI: 10.1515/znc-1984-3-405
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of (R)-Amygdalin and (R)-Vicianin by Partially Purified ß-Glycosidases from Prunus serotina Ehrh. and Davallia trichomanoides

Abstract: Mature black cherry (Prunus serotina Ehrh.) seeds accum ulate high levels of the cyanogenic disaccharide (R)-amygdalin. Extracts from these seeds contain two β-glycosidases which have been identified and completely resolved by DEAE-cellulose ion-exchange chromatography. Amygdalin hydrolase hydrolyzed (R)-am ygdalin at an optimum pH of 5.5, releasing (R)-prunasin and D-glucose. This enzyme showed highest activity towards (R)-am ygdalin and failed to hydrolyze (R)-prunasin. linamarin, β-gentiobiose and cellobios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Previous reports on the presence of diglycosides suggested that the glycosides identified are probably glucose-based and predominantly exist as the -(1 6) linkage [19,21,[30][31][32]. In order to confirm this, we analyzed selected glycosides by ion-mobility MS (IM-MS), a rapid and sensitive technique that separates gas phase ions based on their mobility (inversely proportional to a molecules collision cross-section area) as they traverse through an inert buffer gas [33, for review see 34].…”
Section: Ion-mobility Ms Characterization Of Cyanogenic Glycosides Anmentioning
confidence: 92%
“…Previous reports on the presence of diglycosides suggested that the glycosides identified are probably glucose-based and predominantly exist as the -(1 6) linkage [19,21,[30][31][32]. In order to confirm this, we analyzed selected glycosides by ion-mobility MS (IM-MS), a rapid and sensitive technique that separates gas phase ions based on their mobility (inversely proportional to a molecules collision cross-section area) as they traverse through an inert buffer gas [33, for review see 34].…”
Section: Ion-mobility Ms Characterization Of Cyanogenic Glycosides Anmentioning
confidence: 92%
“…It can occur in one step by a simultaneous mechanism (8) producing a disaccharide and the aglycon or by the sequential mechanism (8), where the two sugars are split off from the diglucoside one after the other in two steps. It can be shown that the simultaneous but not the sequential mechanism is realized in Hevea.…”
Section: Methodsmentioning
confidence: 99%
“…the sequential action of the enzymes AH2, PH, and MDL (12,29). One of the complexities of the Prunus cyanogenic system yet to be satisfactorily unraveled is the microheterogeneity shown by these catabolic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Monospecific antisera deemed suitable for immunocytochemistry and screening of expression libraries were obtained by affinity chromatography. Each antiserum recognized all known isozymes of the specific glucosidase used as antigen.the sequential action of the enzymes AH2, PH, and MDL (12,29). One of the complexities of the Prunus cyanogenic system yet to be satisfactorily unraveled is the microheterogeneity shown by these catabolic enzymes.…”
mentioning
confidence: 99%